Civil liability arising from FIDIC construction contracts and the role of judicial authorities and commercial arbitration according to the regulations in the Kingdom of Saudi Arabia - Mohammed Ahmed Al-Omari (International Journal of Law Research and Studies, 2026)
This research examines the civil liability arising from construction contracts based on FIDIC forms and the extent to which such liability affects contractual relationship between parties. FIDIC contracts are widely used in major construction projects, particularly those involving governmental entities or large corporate contractors, globally and locally. Owing their practical significance and extensive application, these contracts give rise to numerous binding obligations and legal responsibilities for the contracting parties. The study concludes several keys recommendations, most notably the necessity of establishing a regulatory framework for FIDIC contracts through unified electronic platforms, inspired by successful experience of “Ejar” platform. Such platforms would provide standardized and reliable contractual formats with enforceable legal status before judicial authorities, enabling documentation of all stages of contract from inception to completion. This approach would facilitate verification of parties’ compliance with contractual terms and allow for systematic allocation of liability to the defaulting party, thereby reducing time and effort, limiting the burden on courts and arbitration centers, and preventing disputes that could otherwise be effectively regulated and controlled. Furthermore, research highlights the role of Saudi Civil Transactions Law in organizing contractual relationships in general, particularly in defining obligations, their legal consequences, and grounds for exemption from liability in construction contracts. The study also addresses the Sharia and legal validity of FIDIC contracts and examines the mechanisms for dispute resolution, whether before general courts or through arbitration procedures in Kingdom of Saudi Arabia.